2019
DOI: 10.1253/circj.cj-19-0255
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Commonly Examined Parameters Is a Useful Predictor of Positive <sup>99 m</sup>Tc-Labeled Pyrophosphate Scintigraphy Findings in Elderly Patients With Suspected Transthyretin Cardiac Amyloidosis

Abstract: potential benefit from emerging therapies. 2 It has been reported that 13% of elderly patients (mean age, 82 years) who have heart failure with preserved ejection fraction (HFpEF) are diagnosed with ATTRwt. 3 Several postmortem studies found cardiac amyloid deposition in up to 25% of individuals over 80 years of age. 4 The precise diagnosis of CA requires endomyocardial biopsy (EMB) to demonstrate disease-specific deposition. However, EMB is a relatively invasive procedure 5 and so cannot be performed routinel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
59
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 38 publications
(63 citation statements)
references
References 31 publications
(14 reference statements)
1
59
2
Order By: Relevance
“…This may have contributed to an increased number of diagnoses, especially in these several years; however, histologically diagnosed groups equally increased during this period. Previously, we reported that hs‐cTnT could be a clue in early diagnosis 29 and suggested the application of the Kumamoto criteria, 30 a minimally invasive approach for predicting the probability of 99m Tc‐PYP positivity with a combination of electrophysiological (QRS width), structural (left ventricular posterior wall thickness), and biochemistry (hs‐cTnT level) parameters. These practices equally contributed to increasing the number of diagnoses in our institution.…”
Section: Discussionmentioning
confidence: 99%
“…This may have contributed to an increased number of diagnoses, especially in these several years; however, histologically diagnosed groups equally increased during this period. Previously, we reported that hs‐cTnT could be a clue in early diagnosis 29 and suggested the application of the Kumamoto criteria, 30 a minimally invasive approach for predicting the probability of 99m Tc‐PYP positivity with a combination of electrophysiological (QRS width), structural (left ventricular posterior wall thickness), and biochemistry (hs‐cTnT level) parameters. These practices equally contributed to increasing the number of diagnoses in our institution.…”
Section: Discussionmentioning
confidence: 99%
“…4 We previously reported that multiple red flags for amyloid cardiomyopathy, including a high hs-cTnT level, high LV PWTd, and wide QRS, were useful to raise the pretest probability of 99m Tc-PYP positivity. 5 However, patients with multiple red flags for cardiomyopathy were thought have advanced ATTR-CM. Thus, ATTR-CM must be diagnosed before these factors have been completely determined.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this thinking, we believe that the Kumamoto criteria are useful for the W e read with great interest the research article by Tsutsui et al 1 and letter from Kubota et al, as comments on our recent paper. 2 We agree that it is crucial to validate the significance of our recently proposed Kumamoto criteria using other cohorts. Based on their results, they recommend not ruling out transthyretin amyloid cardiomyopathy (ATTR-CM) even in patients with a low score (0, 1) on the Kumamoto criteria.…”
mentioning
confidence: 53%
“…As that point is very important, we also discussed that patients with history of carpal tunnel syndrome or known transthyretin mutation should be consider for 99 m Tc-labeled pyrophosphate ( 99 m Tc-PYP) scintigraphy even if their score is low for the early detection of ATTR-CM. 2 Tsutsui et al 1 performed 99 m Tc-PYP scintigraphy as a "screening" diagnosis for ATTR-CM among elderly patients with heart failure without evident coronary or valvular heart disease. Left ventricular hypertrophy (LVH) was not considered as an inclusion criterion in their study.…”
mentioning
confidence: 99%